1993
DOI: 10.1021/ma00069a031
|View full text |Cite
|
Sign up to set email alerts
|

All-aromatic hyperbranched polyesters with phenol and acetate end groups: synthesis and characterization

Abstract: This report describes the synthesis of all-aromatic hyperbranched polyesters with phenol and acetate end groups. The synthesis was based on the melt condensation of tbe A¡B monomers 3,5-bis-(trimethylsiloxy)benzoyl chloride (2) and 3,5-diacetoxybenzoic acid (3). The trimethylsilyl groups of the polyesters from monomer 2 are hydrolyzed during workup, resulting in polymers with phenol terminal groups. Although the acetate groups of polymers prepared from 3 are quite stable and remain in the polymer, conditions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
233
1
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(257 citation statements)
references
References 7 publications
20
233
1
3
Order By: Relevance
“…In early syntheses of hyperbranched polymers, reactions of monomers ABx (x ≥ 2) where the A and B groups can condense with each other exclusively resulted in step-growth polymerization becoming a predominant method. Thus, an enormous numbers of different types of hyperbranched polymers have been synthesized, including polyphenylenes [8,9], polyesters [10][11][12], polyether [13,14], polysiloxysilanes [15], and polybenzamides [16,17], a variety of which have been reviewed [18,19]. Through conventional step-growth mechanisms, hyperbranched polymers can be synthesized in one-pot, avoiding the need for multiple reactions with protection, deprotection, and purification steps typically required for constructing perfect dendrimers, but with the drawback of large polydispersities in molecular weight and structure.…”
Section: Introductionmentioning
confidence: 99%
“…In early syntheses of hyperbranched polymers, reactions of monomers ABx (x ≥ 2) where the A and B groups can condense with each other exclusively resulted in step-growth polymerization becoming a predominant method. Thus, an enormous numbers of different types of hyperbranched polymers have been synthesized, including polyphenylenes [8,9], polyesters [10][11][12], polyether [13,14], polysiloxysilanes [15], and polybenzamides [16,17], a variety of which have been reviewed [18,19]. Through conventional step-growth mechanisms, hyperbranched polymers can be synthesized in one-pot, avoiding the need for multiple reactions with protection, deprotection, and purification steps typically required for constructing perfect dendrimers, but with the drawback of large polydispersities in molecular weight and structure.…”
Section: Introductionmentioning
confidence: 99%
“…Within other efforts, a monotonic increase of ͓ ͔ with N more akin to the Mark-Houwink behavior of linear polymers was observed, regardless of the degree of branching. [7][8][9][10] The conflicting message of these measurements may in part be due to the difficulty associated with characterizing these materials using size exclusion chromatography ͑SEC͒. The noted polydispersities in N and DB complicate the interpretation of SEC applied to HPs since a highly branched molecule with a large value of N can have the same hydrodynamic volume as a less branched or linear molecule with a smaller value of N.…”
Section: Introductionmentioning
confidence: 99%
“…This value is not far from the theoretically predicted value of 0.5 for very high molar mass polymers. Turner et al 42,43 and Sunder et al 44 earlier prepared hyperbranched polyesters that they reported had DB values of 0.50-0.59. Therefore, it is concluded Poly (12, 2) possesses a hyperbranched structure.…”
Section: Resultsmentioning
confidence: 99%